Perception of factors affecting tropical forage grass seed production in Argentina - Tomas, Maria Andrea; Mattera, Juan (2019)
In Argentina there is an extended region where tropical pastures have shown adaptation to diverse stresses and climate change. Despite their potential role in livestock systems tropical pastures have been underutilized, mainly by limitations of adequate seed availability and quality. The objective was evaluate the perception of people involved in seed production of tropical grass species.